2017
DOI: 10.1007/s10964-017-0756-7
|View full text |Cite
|
Sign up to set email alerts
|

The Happiest Kids on Earth. Gender Equality and Adolescent Life Satisfaction in Europe and North America

Abstract: Cross-national differences in adolescent life satisfaction in Europe and North America are consistent, but remain poorly understood. While previous studies have predominantly focused on the explanatory role of economic factors, such as national wealth and income equality, they revealed weak associations, at most. This study examines whether societal gender equality can explain the observed cross-national variability in adolescent life satisfaction. Based on the assumption that gender equality fosters a support… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
66
5
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(84 citation statements)
references
References 52 publications
6
66
5
5
Order By: Relevance
“…Data from the HBSC 2010 survey revealed that the mean Cantril Ladder scores for all countries was 7.58 and that 28 of 31 countries had a mean value between 7 and 8 (Looze, Huijts, Stevens, Torsheim, & Vollebergh, 2018). This indicates that to understand variation over time and to study differences in measures related to positive mental health, more ambitious cut-off points may provide further information regarding adolescent life satisfaction using the Cantril Ladder -an assertion supported by other scholars (Proctor, Linley, & Maltby, 2010).…”
Section: Introductionmentioning
confidence: 81%
See 2 more Smart Citations
“…Data from the HBSC 2010 survey revealed that the mean Cantril Ladder scores for all countries was 7.58 and that 28 of 31 countries had a mean value between 7 and 8 (Looze, Huijts, Stevens, Torsheim, & Vollebergh, 2018). This indicates that to understand variation over time and to study differences in measures related to positive mental health, more ambitious cut-off points may provide further information regarding adolescent life satisfaction using the Cantril Ladder -an assertion supported by other scholars (Proctor, Linley, & Maltby, 2010).…”
Section: Introductionmentioning
confidence: 81%
“…When studying relatively similar countries, the individual-level factors associated with having high life satisfaction may be of less importance in explaining the country-level differences, especially when studying trends over time. A range of contextual factors have been shown to be associated with the prevalence of child and adolescent life satisfaction, among these socioeconomic and gender equality, acculturation, cultural values and factors related to school (Chu et al, 2010;Jose, Ryan, & Pryor, 2012;Lim et al, 2017;Looze et al, 2018;Proctor et al, 2008;Tov & Diener, 2009).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The national differences among the Nordic countries will be analysed using additional statistic as per previous HBSC studies. One example is the analysis of gender equality, where linear multilevel regression analyses indicated that adolescents in countries with relatively high levels of gender equality report higher life satisfaction than their peers in countries with lower levels of gender equality (de Looze et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Gender equality is defined by UN Women as the equal rights, responsibilities and opportunities of women and men and girls and boys [23]. It is considered an important determinant of population health [24] including different aspects of adolescent mental health [25]. One multi-country study showed higher national gender equality to be associated with higher life-satisfaction among adolescents in Europe and North America.…”
Section: Introductionmentioning
confidence: 99%